Aberrant cytoplasmic connexin43 expression as a helpful marker in vascular neoplasms. (10th June 2021) - Frings, Verena Gerlinde; Goebeler, Matthias; Schilling, Bastian; Kneitz, Hermann
Abstract: Background: Gap junctions consisting of connexins (Cx) are fundamental in controlling cell proliferation, differentiation, and cell death. Cx43 is the most broadly expressed Cx in humans and is attributed an important role in skin tumor development. Its role in cutaneous vascular neoplasms is yet unknown. Methods: Fifteen cases each of cutaneous angiosarcoma (cAS), Kaposi sarcoma (KS), and cherry hemangioma (CH) were assessed by immunohistochemistry for expression of Cx43. Expression pattern, intensity, and percentage of positively stained cells were analyzed. Solid basal cell carcinomas served as positive and healthy skin as negative controls. Results: Most cases of cAS presented with a strong Cx43 staining of almost all tumor cells, whereas endothelia of KS showed medium expression and CH showed mostly weak expression. In comparison with KS or cAS, the staining intensity of CH was significantly lower ( P  ≤ 0.001). All tissue sections of both cAS and KS were characterized by a mostly diffuse, cytoplasmic staining pattern of the vascular endothelia. None of those showed nuclear staining. Conclusion: The high‐to‐intermediate expression of Cx43 observed in all cases of cAS and KS suggests that this Cx may play a role in the development of malignant vascular neoplasms and serve as a helpful diagnostic marker.